2019
DOI: 10.14202/vetworld.2019.483-488
|View full text |Cite
|
Sign up to set email alerts
|

Effect of citrus waste on blood parameters of broiler birds with and without cocktail of enzymes

Abstract: Aim: This study aimed to assess the effect of different levels of citrus waste (CW) with or without enzyme cocktail on blood profile of broilers. Materials and Methods: CW was sun-dried and grounded to powder CW. 256-day-old birds were distributed into eight groups; control (C), CW-supplemented diets (2.5% CW, 5.0% CW, and 7.5% CW), enzyme (E) cocktail supplemented diets (CE, 2.5% CWE, 5.0% CWE, and 7.5% CWE). The diets were fed during starter (0-14 days), grower (15-21 days), and finisher (22-42 days) phases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…Absence of significant differences in the serum parameters between the control and SOPP treatment groups in this study suggests that the dosage of SOPP did not adversely affect the serum indices and organ function. This finding agrees with the report of Behera et al (2019), who did not find significant (p ≤ 0.05) difference in glucose, TP, ALB, and globulin level of broilers fed 2.5 to 7.5 % of citrus waste for 7 weeks. Likewise, Abbasi et al (2015) reported no effect of dried citrus sinensis pulp in the diet of broiler birds on the serum enzyme activities (ALT and AST), which is an indication of no organ toxicity.…”
Section: Discussionsupporting
confidence: 93%
“…Absence of significant differences in the serum parameters between the control and SOPP treatment groups in this study suggests that the dosage of SOPP did not adversely affect the serum indices and organ function. This finding agrees with the report of Behera et al (2019), who did not find significant (p ≤ 0.05) difference in glucose, TP, ALB, and globulin level of broilers fed 2.5 to 7.5 % of citrus waste for 7 weeks. Likewise, Abbasi et al (2015) reported no effect of dried citrus sinensis pulp in the diet of broiler birds on the serum enzyme activities (ALT and AST), which is an indication of no organ toxicity.…”
Section: Discussionsupporting
confidence: 93%
“…Biochemical assay kits from Erba diagnostics Mannheim GmbH, Germany, were used to analyze bilirubin total, creatinine, triglycerides, total protein, uric acid and SGOT (Serum glutamicoxaloacetic transaminase) from plasma samples of birds in different LAN treatment phases. The kit is widely used in assessing the different biochemical parameters in mammalian and avian model systems (Shivprasad et al, 2014, Behera et al, 2019, Khandia et al, 2020. All samples were diluted in the ratio of 1:3 (plasma: distilled water) to attain sufficient volumes for running all the tests.…”
Section: Biochemical Parametersmentioning
confidence: 99%
“…Although OH does not have significant amounts of starch and protein [ 2 , 8 ], its extrusion may change its particle size and cause a redistribution of its fiber components, thereby creating a differential effect on gut microbiota than coarse OH. Various dietary fiber types have been reported to differentially affect blood biochemical parameters [ 19 , 20 , 21 , 22 ] with soluble fiber observed to reduce the concentrations of triglycerides, phospholipids, and low density lipoprotein (LDL) cholesterol in the blood [ 23 , 24 , 25 ]. The objective of this study, therefore, was to determine the effect of coarse and extruded OH on growth performance, blood biochemical characteristics, and cecal SCFA and microbiota in broiler chickens.…”
Section: Introductionmentioning
confidence: 99%